2014
DOI: 10.1080/03079457.2014.966055
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteropathogenic bacteria in common quail (Coturnix coturnix)

Abstract: The study was aimed at evaluating the prevalence of enteropathogenic bacteria (i.e. Campylobacter spp., shigatoxin-producing Escherichia coli, Salmonella spp.) in common quail (Coturnix coturnix). To achieve this goal, 70 common quails were collected during the hunting season in the Campania region (southern Italy). From each bird, cloacal swab samples were collected and subjected to culture methods, polymerase chain reaction and serotyping. The results of the present study showed a prevalence of 21.4% and 5.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
15
1
1
Order By: Relevance
“…It is a common colonizer of the avian digestive tract with no principal effect on the health status of the birds. However, it can be a potential carrier of disease to other animals and humans [53]. In this study, it was detected in a range from 10%-14% abundance in low female/male and 7%-11% in high female/male birds (Figure 3 and Supplementary Table S8).…”
Section: Gender Effects On Microbiota Pu Cau Fi Bwg and Fcmentioning
confidence: 51%
“…It is a common colonizer of the avian digestive tract with no principal effect on the health status of the birds. However, it can be a potential carrier of disease to other animals and humans [53]. In this study, it was detected in a range from 10%-14% abundance in low female/male and 7%-11% in high female/male birds (Figure 3 and Supplementary Table S8).…”
Section: Gender Effects On Microbiota Pu Cau Fi Bwg and Fcmentioning
confidence: 51%
“…In fact, in the present study, it was clearly noticed that C. coli was the dominant species found in quail's flocks/producers after slaughtering, being C. jejuni occasionally detected and cohabitant with C. coli. Also, Dipineto et al (2014) evaluating the prevalence of Campylobacter spp., but in common quail (Coturnix coturnix), referred the dominance of C. coli. This was also observed in turkeys, but contrary to the dominance of C. jejuni found in broilers Kashoma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…quails have a certain degree of resistance to some diseases, they are prone to some poultry diseases and pests [22]. Enteropathogenic bacteria are prevalent among quails [23]. According to the studies [24], quails are prone to the following diseases and pests as shown in (Table 7) and can be classified according to causal agents [25].…”
Section: Feedingmentioning
confidence: 99%